Two-dimensional Bi2MoO6 coated CuFe2O4 nano porous structure cubic photocatalyst

The synthesis of CuFe2O4/Bi2MoO6 nanoporous structure cube photocatalysts through solvent thermal method and MOF self-sacrificing template process, solving the efficiency of CuFe2O4 and Bi2MoO6 in the field of photocatalysis, achieving high specific surface area and high photocatalytic activity, significantly improving the antibiotic degradation efficiency , and secondary pollution is avoided through magnetic separation.

CN119215994APending Publication Date: 2024-12-31CHANGCHUN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411363632.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

CuFe2O4 catalysts have problems such as poor photogenerated carrier separation and transfer capabilities and easy agglomeration in the field of photocatalysis. Bi2MoO6 has low visible light absorption efficiency and slow carrier transmission, which limits its catalytic efficiency. In the existing technology, Bi2MoO6 has not been seen to wrap CuFe2O4. Reports of nanostructured cubes.

Method used

Using the solvent thermal method and MOF self-sacrifice template process, CuFe2O4 porous cubes were synthesized by Prussian blue MOF cubes as templates, and Bi2MoO6 nanosheets were grown on its surface to form CuFe2O4/Bi2MoO6 nanoporous structure cube photocatalyst.

Benefits of technology

The specific surface area and photocatalytic activity of the photocatalyst are significantly improved, the antibiotic degradation efficiency is improved, the degradation rate reaches 98.54%, and secondary pollution is avoided through magnetic separation. The specific surface area and degradation rate of the catalyst are much higher than that of CuFe2O4 and Bi2MoO6 alone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215994A_ABST
    Figure CN119215994A_ABST
Patent Text Reader

Abstract

The invention relates to a two-dimensional Bi2MoO6-coated CuFe2O4 nano-porous structure cubic photocatalyst, which is characterized in that a solvothermal method and an MOF self-sacrifice template process technology are combined, nano-particles with a Prussian blue solid cubic structure are synthesized to serve as a template agent, Cu < 2 + > is ground and uniformly mixed with PB, and then the mixture is calcined at a high temperature to obtain the CuFe2O4 nano-porous structure cubic photocatalyst. According to the CuFe2O4 / Bi2MoO6 nanostructure cube and the preparation method thereof, organic matters such as PVP and cyanide ligands are slowly decomposed and dispersed in a gas form to form a CuFe2O4 cube with a porous structure, finally, Bi2MoO6 nanosheets grow on the outer surface of the CuFe2O4 cube in situ in a solvothermal mode, and a synthetic product is the CuFe2O4 / Bi2MoO6 nanostructure cube. The nano material with the special structure has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the research field of nano material preparation, and in particular to a two-dimensional Bi2MoO6-wrapped CuFe2O4 nanostructured cubic photocatalyst. Background Art

[0002] In recent years, researchers have focused on the synthesis of porous CuFe2O4 nanostructured cubes using a metal organic framework (MOF) self-sacrificial template process. The nanoscale shell structure prepared by this method usually has excellent morphology, large specific surface area, and fast charge carrier conduction speed. This unique structure has been proven to have extraordinary performance in energy storage, catalysis, lithium storage and other fields.

[0003] As a magnetic material, CuFe2O4 can not only prolong the service life of the catalyst, but also make up for the disadvantage of the difficulty in recycling traditional powder catalysts, so that it can be reused and reduce pollution. However, there are many problems when CuFe2O4 is used as a catalyst, such as poor separation and transfer ability of photogenerated carriers, easy agglomeration, etc., which still limit the catalytic efficiency of CuFe2O4. Therefore, many efforts are devoted to inhibiting the recombination of photogenerated electrons and holes and enhancing the absorption of visible light. Among various semiconductor materials, bismuth-based photocatalysts, as a visible light responsive photocatalyst, have the advantages of low cost, non-toxicity, and excellent photochemical properties, and have attracted widespread attention from researchers. The most representative of them is bismuth molybdate (Bi2MoO6), which is a typical and energy-rich n-type Aurivillius oxide, which has attracted widespread attention due to its layered structure and high stability. Despite this, the catalytic efficiency of Bi2MoO6 is still limited by low visible light absorption efficiency and slow carrier transport. Therefore, it is necessary to modify Bi2MoO6 to improve its photocatalytic activity. The energy band structure of Bi2MoO6 can be cross-matched with that of CuFe2O4. Constructing a heterojunction between the two can inhibit the recombination of electrons and holes to a certain extent and improve its photocatalytic efficiency. There are currently no reports on Bi2MoO6 encapsulating CuFe2O4 nanostructured cubes.

[0004] Metal-organic frameworks (MOFs) are emerging porous materials that have developed rapidly in recent years. Due to their ordered and regular structure, high specific surface area and adjustable structure, their structure can be regarded as a central metal connected and assembled by organic ligands, which makes them have obvious advantages and more attractive application prospects than traditional porous materials, such as: a wide variety, strong functionality, high specific surface area and porosity, and adjustable structure. At present, MOFs have been widely used in gas adsorption, separation, heterogeneous catalytic reactions, optoelectronics and magnetism, drug release and sensors. However, since MOFs are three-dimensional network structure crystals formed by hybridization of coordination bonds with inorganic metal centers, although the pore structure of MOFs is similar to that of zeolites, the framework is flexible. Therefore, compared with other porous materials, the stability of MOFs materials is generally poor, so the practical application of this material has been limited. The characteristics of MOFs materials that are easily decomposed by heat can be used to prepare stable nanoporous carbon materials by high-temperature calcination and carbonization. MOFs are used as sacrificial templates to prepare nanoporous carbon materials in energy, environment and catalysis. The invention adopts a sacrificial template method to synthesize a Prussian blue MOF nanostructured cube and then uses a solvent thermal method to grow a two-dimensional Bi2MoO6 nanosheet on its surface. The synthesized CuFe2O4 / Bi2MoO6 has excellent photocatalytic performance in degrading antibiotics. Summary of the invention

[0005] In order to provide a simple and convenient preparation technology for a two-dimensional Bi2MoO6-wrapped CuFe2O4 nanoporous structure cube photocatalyst with high specific surface area and high photocatalytic activity in the field of photocatalytic degradation, we combined the solvothermal method with the MOF self-sacrificial template process technology and invented a new method for preparing CuFe2O4 / Bi2MoO6 nanoporous structure cubes with high photocatalytic activity.

[0006] The present invention is achieved by synthesizing Prussian blue solid cubic structure nanoparticles as a template, and Cu 2+ By grinding and uniformly mixing with PB and then calcining at high temperature, organic matter such as PVP and cyanide ligands slowly decompose and disperse in the form of gas to form a porous CuFe2O4 cube. Then, Bi2MoO6 nanosheets are in situ grown on the outer surface of the CuFe2O4 cube by solvent thermal method. The synthetic product is CuFe2O4 / Bi2MoO6 nanostructured cube. The specific steps are as follows:

[0007] (1) Preparation of Fe4(Fe(CN)6)3 Prussian blue (PB) cubes containing iron MOF

[0008] In 250mL HCl solution (0.1mol·L -1) was added with 15 g of polyvinyl pyrrolidone (PVP, K30), and a clear solution was obtained after magnetic stirring for 30 min. 0.6 g of K4FeC6N6·3H2O was added to the above solution, and stirring was continued for 30 min to obtain a clear light yellow solution, which was then transferred to a sealed container and kept in an oven at 80°C for 24 h. The obtained blue product was allowed to precipitate and then washed three times with ethanol (EtOH) and distilled water. The sample was dried in a vacuum oven at 70°C for 12 h.

[0009] (2) Preparation of CuFe2O4 porous cubes

[0010] 0.2 g Fe-based MOFs precursor and 0.193 g copper nitrate trihydrate were dispersed in 40 mL ethanol under constant stirring. The solution temperature was raised to 70 °C. After all the ethanol was evaporated, the product was collected and fully ground, and then heated to 700 °C in air at a heating rate of 2 °C min. -1 , keep warm for 6h.

[0011] (3) CuFe2O4 / Bi2MoO6 (CFO / BMO) composite photocatalyst

[0012] A certain amount of Na2MoO4·2H2O and Bi(NO3)3·5H2O were dissolved in 5mL ethylene glycol (EG), respectively, and were recorded as solution A and solution B. Then, solution B was slowly dripped into solution A, and 30mL EtOH and 0.1g CuFe2O4 cubes were added and stirred for 30min. The mixed solution was transferred to a 100mL stainless steel autoclave lined with polytetrafluoroethylene, kept at 160℃ for 24h, and naturally cooled to room temperature. The obtained CFO / BMO was washed several times with deionized water and EtOH, respectively, and dried at 60℃ for 8h. The composites with different ratios were named CFO / BMO-1, CFO / BMO-2 and CFO / BMO-3. For comparison, pure Bi2MoO6 was prepared under the same conditions, but without adding CuFe2O4 cubes. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a SEM photo of CFO / BMO, which also serves as an abstract figure;

[0014] Figure 2 It is the XRD spectra of CuFe2O4, Bi2MoO6 and CFO / BMO composites with different ratios;

[0015] Figure 3 are the N2 adsorption-desorption isotherms of CuFe2O4, Bi2MoO6 and CFO / BMO-2;

[0016] Figure 4This is the performance diagram of photocatalytic removal of tetracycline by CuFe2O4, Bi2MoO6 and composites with different ratios of CFO / BMO;

[0017] Figure 5 The kinetic fitting curves of photocatalytic removal of tetracycline by CuFe2O4, Bi2MoO6 and composites with different ratios of CFO / BMO are shown;

[0018] Figure 6 are the magnetization curves of CuFe2O4 and CFO / BMO-2;

[0019] Figure 7 It is a possible degradation pathway for the photocatalytic removal of tetracycline by CFO / BMO-2. DETAILED DESCRIPTION

[0020] The Na2MoO4·2H2O, Bi(NO3)3·5H2O, Cu(NO3)2·3H2O, Fe(NO3)3·9H2O selected by the present invention have a purity of 99.00%, the purity of potassium ferrocyanide is 99.00%, polyvinylpyrrolidone PVP, molecular weight is 58000, N,N-dimethylformamide DMF, all of which are commercially available analytical pure products; the glass instruments, crucibles and equipment used are instruments and equipment commonly used in laboratories.

[0021] Example: SEM photo of CuFe2O4 / Bi2MoO6 composite Figure 1 As shown, Bi2MoO6 nanosheets are densely anchored around the cube, and the length, width and height of the cube are about 300×300×300nm. The phase composition and crystal structure of the prepared photocatalyst were characterized by XRD. Figure 2As shown, the diffraction peaks at 18.3°, 29.9°, 34.7°, 35.8°, 43.7°, 57.8° and 62.1° in CuFe2O4 cubes correspond to the (101), (112), (103), (211), (220), (321) and (224) crystal planes of tetragonal CuFe2O4 (PDF#34-0425), respectively, while the diffraction peaks at 28.2°, 32.6°, 47.1° and 55.5° for pure Bi2MoO6 nanosheets correspond to the (131), (002), (062) and (133) crystal planes of orthorhombic Bi2MoO6 (PDF#72-1524). When Bi2MoO6 nanosheets grow on the surface of CuFe2O4 cubes, the characteristic peaks of Bi2MoO6 and CuFe2O4 appear in the CuFe2O4 / Bi2MoO6 composite sample, revealing the successful combination of Bi2MoO6 and CuFe2O4. At the same time, with the increase of Bi2MoO6 loading, the intensity of the characteristic peak of Bi2MoO6 in the composite also increases. No peaks representing impurities were detected, which means that the composite material has good crystallinity and purity. Specific surface area is an important physical characteristic of photocatalysts and one of the main factors affecting the efficiency of photocatalytic degradation. Therefore, the specific surface area of ​​Bi2MoO6, CuFe2O4 and CuFe2O4 / Bi2MoO6 composite catalysts was analyzed by N2 adsorption-desorption isotherms. The CuFe2O4 / Bi2MoO6 composite shows a typical type IV isotherm with the presence of an H3-type hysteresis loop ( Figure 3 ), indicating the formation of its mesoporous structure. The specific surface area of ​​Bi2MoO6 is about 25.9m 2 g -1 , composite with CuFe2O4 (58.7m 2 g -1 The specific surface area of ​​CuFe2O4 / Bi2MoO6 composite photocatalyst (89.6 m 2 g -1 ) increased significantly. This may be due to the fact that the combination of Bi2MoO6 nanolayers and CuFe2O4 cubes increased the contact area and further increased the number of active sites, thereby increasing its adsorption capacity for tetracycline hydrochloride (TC).

[0022] The photocatalytic performance of the prepared catalysts was evaluated by testing the degradation of TC in water under simulated sunlight. Figure 4 As shown in Figure 2, it was observed that the sample reached adsorption equilibrium after stirring for 30 min in the dark. After 30 min of illumination, the degradation rate of CFO / BMO-2 reached 98.54%. By further analyzing the photodegradation curve of TC, Figure 5As shown in Figure 2, it was found that ln(C0 / Ct) was approximately linearly related to the illumination time, proving that its reaction kinetics conformed to the pseudo-first-order kinetic model. The CuFe2O4 / Bi2MoO6 composite exhibited the highest TC photodegradation rate constant (k = 0.104min -1 ), respectively, than CuFe2O4 (0.026min -1 ) and Bi2MoO6(0.022min -1 ) are nearly 4 and 4.7 times larger. The hysteresis loops of CuFe2O4 and CFO / BMO-2 at 25°C are shown in Figure 6 As shown in Figure 2, the magnetization intensities of CFO / BMO-2 and CuFe2O4 are 10.96 and 15.09 emu g, respectively. -1 . Although the magnetism decreases slightly after forming a heterojunction composite photocatalyst, after the photocatalytic reaction, CFO / BMO-2 can be quickly precipitated and separated by a magnet, avoiding secondary pollution of the water body by the powder material after the reaction. In addition, in order to study the photocatalytic degradation pathway of TC by the CuFe2O4 / Bi2MoO6 composite, liquid chromatography-mass spectrometry (HPLC-MS) was used to monitor the degradation process and detect the intermediates. With the extension of the reaction time, the intensity of the peak corresponding to TC (m / z=445) was significantly weakened, while the number of small molecule peaks increased and the intensity increased. Based on the main intermediates detected, two possible transformation pathways for TC photodegradation were proposed ( Figure 7 In path 1, TC (m / z = 445) is easily attacked by ·OH radicals due to its high electron density on the double bond, producing an intermediate P1 (m / z = 461). The free radical then attacks the -N(CH3)2 group to generate P2 (m / z = 432), and the intermediate product is further attacked by ·O2 - Free radical oxidation generates dealkylation and deamination products P3 (m / z = 383) and P4 (m / z = 362). P4 (m / z = 362) undergoes a series of dehydroxylation and ring-opening reactions to generate P5 (m / z = 318). In path 2, TC (m / z = 445) undergoes hydroxylation to generate intermediate P6 (m / z = 477), which continues to undergo multiple elimination reactions to generate P7 (m / z = 361) and compound P8 (m / z = 272). The loss of methyl and amide groups in intermediate P6 (m / z = 477) converts it to P9 (m / z = 392), which can be converted to product P10 (m / z = 344) through further functional group loss, and P10 (m / z = 344) generates product P11 (m / z = 241) through ring-opening reaction. All intermediates are eventually oxidized to CO2 and H2O.

[0023] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.

Claims

1. A two-dimensional Bi2MoO6-wrapped CuFe2O4 nanoporous structure cubic photocatalyst, characterized in that: The porous cubic particles have uniform size, large specific surface area, strong light absorption capacity, and dimensions of approximately 300×300×300nm in length, width, and height. Under simulated sunlight conditions, they have good photocatalytic degradation performance of tetracycline (TC).

2. A method for preparing a two-dimensional Bi2MoO6-wrapped CuFe2O4 nanoporous structure cubic photocatalyst, characterized in that: The solvothermal method and MOF self-sacrificial template process were combined to synthesize Prussian blue solid cubic structure nanoparticles as templates. 2+ By grinding and uniformly mixing with PB and then calcining at high temperature, organic matter such as PVP and cyanide ligands slowly decompose and disperse in the form of gas to form a porous CuFe2O4 cube. Then, Bi2MoO6 nanosheets are in situ grown on the outer surface of the CuFe2O4 cube by solvent thermal method. The synthetic product is CuFe2O4 / Bi2MoO6 nanostructured cube. The specific steps are as follows: (1) Preparation of Fe4(Fe(CN)6)3 Prussian blue (PB) cubes containing iron MOF In 250mL HCl solution (0.1mol·L -1 ) was added with 15 g of polyvinyl pyrrolidone (PVP, K30), and a clear solution was obtained after magnetic stirring for 30 min. 0.6 g of K4FeC6N6·3H2O was added to the above solution, and stirring was continued for 30 min to obtain a clear light yellow solution, which was then transferred to a sealed container and kept in an oven at 80°C for 24 h. The obtained blue product was allowed to settle and then washed three times with ethanol (EtOH) and distilled water. The sample was dried in a vacuum oven at 70°C for 12 h; (2) Preparation of CuFe2O4 porous cubes 0.2 g Fe-based MOFs precursor and 0.193 g copper nitrate trihydrate were dispersed in 40 mL ethanol under constant stirring. The solution temperature was raised to 70 °C. After all the ethanol was evaporated, the product was collected and fully ground, and then heated to 700 °C in air at a heating rate of 2 °C min. -1 , keep warm for 6h; (3) CuFe2O4 / Bi2MoO6 (CFO / BMO) composite photocatalyst A certain amount of Na2MoO4·2H2O and Bi(NO3)3·5H2O were dissolved in 5mL of ethylene glycol (EG), respectively, and were recorded as solution A and solution B. Then, solution B was slowly dripped into solution A, and 30mL of EtOH and CuFe2O4 cubes were added and stirred for 30min. The mixed solution was transferred to a 100mL stainless steel autoclave lined with polytetrafluoroethylene and kept at 160℃ for 24h. After naturally cooling to room temperature, the obtained CFO / BMO was washed several times with deionized water and EtOH, respectively, and dried at 60℃ for 8h. Pure Bi2MoO6 was prepared under the same conditions, but without adding CuFe2O4 cubes. Using the solvent method and MOF self-sacrificial template process, two-dimensional Bi2MoO6 nanosheets were grown on the surface of CuFe2O4 cubes to form CFO / BMO nanoporous structure cubes. This structure avoids large-scale agglomeration of nanosheets during the reaction and ensures high specific surface area to the greatest extent. Under simulated sunlight, the TC degradation efficiency of CFO / BMO reaches 98.54% within 30 minutes. In addition, CFO / BMO also has good magnetic properties and can be separated from the solution by a magnet after the photocatalytic reaction is completed, avoiding secondary pollution. After five cycle tests, the color, performance and crystal structure of the photocatalyst did not change significantly, and it has good reusability.